Exosomal lncRNA GAS5 regulates the apoptosis of macrophages and vascular endothelial cells in atherosclerosis - Chen, Lei; Yang, Wenjin; Guo, Yijun; Chen, Wei; Zheng, Ping; Zeng, Jinsong; Tong, Wusong (PloS one, 2017)
Atherosclerosis is universally recognized as a chronic lipid-induced inflammation of the vessel wall. Oxidized low density lipoprotein (oxLDL) drives the onset of atherogenesis involving macrophages and endothelial cells (ECs). Our earlier work showed that expression of long noncoding RNA-growth arrest-specific 5 (lncRNA GAS5) was significantly increased in the plaque of atherosclerosis collected from patients and animal models. In this study, we found that knockdown of lncRNA GAS5 reduced the apoptosis of THP-1 cells treated with oxLDL. On the contrary, overexpression of lncRNA GAS5 significantly elevated the apoptosis of THP-1 cells after oxLDL stimulation. The expressions of apoptotic factors including Caspases were changed with lncRNA GAS5 levels. Moreover, lncRNA GAS5 was found in THP-1 derived-exosomes after oxLDL stimulation. Exosomes derived from lncRNA GAS5-overexpressing THP-1 cells enhanced the apoptosis of vascular endothelial cells after taking up these exosomes. However, exosomes shed by lncRNA GAS5 knocked-down THP-1 cells inhibited the apoptosis of endothelial cells. These findings reveal the function of lncRNA GAS5 in atherogenesis which regulates the apoptosis of macrophages and endothelial cells via exosomes and suggest that suppressing the lncRNA GAS5 might be an effective way for the therapy of atherosclerosis.